DisOrientations German-Turkish Cultural Contact in Translation, 1811-1946. - Dickinson, Kristin (Max Kade Research Institute: Germans Beyond Europe., 2021)
"Explores the German-Turkish literary-cultural relationship from 1811 to 1946, focusing on literary translation as a complex mode of cultural, political, and linguistic orientation"--